An Update on Antiviral Therapy Against SARS-CoV-2: How Far Have We Come? - Indari, Omkar; Jakhmola, Shweta; Manivannan, Elangovan; Jha, Hem Chandra (Frontiers in Pharmacology, 2021)
COVID-19 pandemic has spread worldwide at an exponential rate affecting millions of people instantaneously. Currently, there is no specific drug or vaccine available various drugs are under investigation to treat an enormously increasing number of COVID-19 patients. This dreadful situation clearly demands an efficient strategy to quickly identify drugs for the successful treatment of COVID-19. Hence, drug repurposing is an effective approach for the rapid discovery of frontline arsenals to fight against COVID-19. Successful application of this approach has resulted in the repurposing of some clinically approved drugs as potential anti-SARS-CoV-2 candidates. Several of these drugs are either antimalarials, antivirals, antibiotics or corticosteroids and they have been repurposed based on their potential to negate virus or reduce lung inflammation. Large numbers of clinical trials have been registered to evaluate the effectiveness and clinical safety of these drugs. Till date, a few clinical studies are complete and the results are primary. WHO also conducted an international, multi-country, open-label, randomized trials- a solidarity trial for four antiviral drugs. However, solidarity trials have few limitations like no placebos were used, additionally any drug may show effectiveness for a particular population in a region which may get neglected in solidarity trial analysis. The ongoing randomized clinical trials can provide reliable long-term follow-up results that will establish both clinical safety and clinical efficacy of these drugs with respect to different regions, populations and may aid up to worldwide COVID-19 treatment research. This review presents a comprehensive update on majorly repurposed drugs namely chloroquine, hydroxychloroquine, remdesivir, lopinavir-ritonavir, favipiravir, ribavirin, azithromycin, umifenovir, and oseltamivir as well as convalescent plasma therapy used; used as antiviral therapy against SARS-CoV-2. The review also summarizes the data recorded on the mechanism of anti-SARS-CoV-2 activity of these repurposed drugs along with the preclinical and clinical findings, therapeutic regimens, pharmacokinetics, and drug-drug interactions.